Program Pemberdayaan Masyarakat Melalui Pelatihan Penggunaan Tang Meter Untuk Keselamatan Instalasi Listrik Rumah Tangga - Reson Wibowo; Nurjaya .; Agus Bayu Utama (CV. ITTC INDONESIA, 2025)
Electrical safety in household installations is a critical issue due to the high incidence of fires caused by electrical faults, particularly in densely populated residential areas. Preliminary observations in RT 006/RW 005 Pamulang revealed that residents had never conducted independent inspections of electrical current and load conditions and lacked the ability to use measuring tools such as clamp meters, resulting in undetected hazards such as overloads and leakage currents. This Community Service Program (PKM) aims to enhance residents’ knowledge and skills in measuring electrical current, identifying potential electrical hazards, and implementing preventive actions in accordance with the PUIL 2011 safety standard. The program employed a participatory–educational approach consisting of initial surveys, preparation of technical materials, tool demonstrations, and hands-on field practice. Evaluation was conducted using pre-test and post-test questionnaires, supported by direct observation of participants’ ability to operate clamp meters during practice sessions. The results indicate a significant improvement in understanding the function of clamp meters, overload risks, and leakage current detection. Participants successfully operated the clamp meter independently, interpreted measurement readings accurately, and identified circuits exceeding safe current limits. This program has effectively increased community awareness of electrical safety and strengthened the application of K3 principles at the household level. It also provides a sustainable training model that can be implemented at the community level.